Person-person transmission of Brucella melitensis - A rare case report (Indian Journal of Case Reports, 2018)
Brucellosis, also known as “undulant fever” and “Mediterranean fever,” is a zoonosis. It is almost invariably transmitted by direct or indirect contact with infected animal tissues or ingestion of their products. It is endemic in many parts of the world and can affect people of all ages and both the sexes. Person-to-person transmission of brucellosis is usually rare. Here, we report the case of human-to-human transmission of brucellosis melitensis presented as a breast abscess.